Undernutrition, socio-demographic characteristics and eating habits of the elderly - Millimono, Thierno Mamadou; Camara, Alioune; Mabiama, Gustave; Toure, Fanta; Sidibé, Sidikiba; Preux, Pierre-Marie; Desport, Jean-Claude; Fayemendy, Philippe; Jésus, Pierre (Clinical nutrition ESPEN, 2024)
Ageing is often accompanied by a decrease of food consumption, possibly leading to undernutrition. A single nutritional study was conducted in 2011 in the general population, showing that 5.5% of people aged >65 years were undernourished. The aim of our study was to assess the prevalence of undernutrition in the elderly and its relationship with sociodemographic characteristics and dietary habits. A cross-sectional study was conducted on a representative sample of subjects aged ≥60 years in urban and rural areas of the country's eight administrative regions. A questionnaire including socio-demographic data, food consumption frequencies and anthropometric measurements was used. Student's t-test and Man Whitney test were used with a significance level of 5%. A multivariate analysis was performed between undernutrition and the other factors collected. 1698 older adults were included (male: 63.5%, sex ratio M/F = 1.7), with a mean age of 71.6 ± 9.4 years and a BMI of 22.6 ± 4.4 kg/m2. The prevalence of undernutrition was 14.4%. Undernutrition was significantly associated with age 80–89 years and ≥90 years, (p = 0.0001 and p = 0.0001 respectively), male sex (p = 0.006), rural areas (p = 0.002), being in activity (p = 0.009) and fish consumption (p = 0.039). Breakfast was consumed every day in 87.2% of cases, lunch in 74.3% and dinner in 83.2%. Rice and bread were the most consumed food. Early detection of nutritional disorders, nutritional education and promotion of a balanced diet could help improve the health of the elderly.